Postoperative Pain of Pediatric Patients Undergoing Dental Treatment under General Anesthesia Visiting a General Hospital: A Cross-Sectional Study - Ateet Kakti; Reema Khalid Abumelha; Asmaa Mansour Alajmi; Lamis Khalid Dagriri; Lamia Abdullah Alkodari; Mohammed. J. Fares; Marco Cicciù; Giuseppe Minervini (MDPI AG, 2023)
Dental general anesthesia (GA) is a day-stay procedure and is a suitable choice for complicated cases. It is undertaken in a controlled hospital setting that ensures the quality, safety, efficacy, and efficiency of dental treatment. The purpose of this study is to determine the prevalence, severity, duration, and factors related to the occurrence of postoperative discomfort in young children following GA in a general hospital. This study includes a minimum sample size of 23 children that were undergoing GA over a 1-month period. Informed consent was obtained from the parent prior to the treatment. A preoperative questionnaire via the Survey Monkey program was used for the purposes of recording the responses of the survey population. All data related to the immediate postoperative period while the child was in the post-anesthetic recovery room (PAR) was collected and assessed by one of the investigators using the Face, Legs, Activity, Cry, and Consolability (FLACC) pain assessment scale. Postoperative data was gathered using the Dental Discomfort Questionnaire (DDQ-8) and was performed by phone 3 days after the GA procedure. The participating 23 children ranged from 4 to 9 years old (mean 5.43 ± 1.53). A total of 65.2% were girls and 34.8% were boys, with 30.4% experiencing a recent history of pain.